Law Enforcement Against Spatial Planning Violations in the Development of Tourism Accommodations on Bingin Beach, Badung Regency - Ni Nyoman Wulan Prasintya Putri; I Wayan Wesna Astara; Ni Komang Arini Setyawati (International Journal of Sociology and Law, 2026)
This study aims to analyze the implementation of spatial planning regulations in the development of tourism accommodations and law enforcement against spatial planning violations in the Bingin Beach area, Badung Regency. The rapid development of tourism in the area has encouraged the construction of various facilities such as villas, hotels, and restaurants, some of which are located in coastal areas and do not fully comply with spatial planning and licensing regulations. This study uses empirical legal research methods with a legislative approach, case approach, and legal sociology approach. Data was obtained through observation, interviews, and document studies, then analyzed qualitatively. The results show that the implementation of spatial planning regulations in Bingin Beach has not been optimal because there are still tourism accommodation buildings that violate zoning and coastal boundary line regulations. This condition is influenced by weak supervision, rapid tourism development, and lack of compliance with licensing procedures. Law enforcement is carried out by the local government through the imposition of administrative sanctions and efforts to control buildings that do not comply with spatial planning. This law enforcement aims to maintain order in the use of space and protect the sustainability of the coastal environment.